High Dose Lopinavir/Ritonavir Does Not Lead to Sufficient Plasma Levels to Inhibit SARS-CoV-2 in Hospitalized Patients With COVID-19 - Karolyi, Mario; Omid, Sara; Pawelka, Erich; Jilma, Bernd; Stimpfl, Thomas; Schoergenhofer, Christian; Laferl, Hermann; Seitz, Tamara; Traugott, Marianna; Wenisch, Christoph; Zoufaly, Alexander (Frontiers in Pharmacology, 2021)
Background: Despite lopinavir/ritonavir (LPV/RTV) demonstrating in-vitro activity against SARS-CoV-2, large trials failed to show any net clinical benefit. Since SARS-CoV-2 has an EC50 of 16.4 µg/mL for LPV this could be due to inadequate dosing. Methods: COVID-19 positive patients admitted to the hospital who received high dose LPV/RTV were included. High dose (HD) LPV/RTV 200/50mg was defined as 4 tablets bid as loading dose, then 3 tablets bid for up to 10 days. Trough plasma concentrations were measured after the loading dose and on day 5-7 in steady state (SS). Post loading dose (PLD) and SS plasma trough levels were compared with SS trough levels from COVID-19 patients who received normal dose (ND) LPV/RTV (2 tablets bid) at the beginning of the pandemic. Results: Fifty patients (30% female) with a median age of 59 years (IQR 49-70.25) received HD LPV/RTV. Median HD-PLD concentration was 24.9 μg/mL (IQR 15.8-30.3) and significantly higher than HD-SS (12.9 μg/mL, IQR 7.2-19.5, p<0.001) and ND-SS (13.6 μg/mL, IQR 10.1-22.2, p=0.013). HD-SS and ND-SS plasma levels did not differ significantly (p=0.507). C-reactive-protein showed a positive correlation with HD-SS (Spearman correlation-coefficient rS=0.42, p=0.014) and ND-SS (rS=0.81, p=0.015) but not with HD-PLD (rS=0.123, p=0.43). Conclusion: HD-PLD plasma trough concentration was significantly higher than HD-SS and ND-SS concentration, but no difference was detected between HD-SS and ND-SS trough levels. Due to the high EC50 of SARS-CoV-2 and the fact that LPV/RTV is highly protein bound, it seems unlikely that LPV/RTV exhibits a relevant antiviral effect against SARS-CoV-2 in vivo.